Inventing Disaster : The Culture of Calamity from the Jamestown Colony to the Johnstown Flood - Kierner, Cynthia A., 1958- (Book collections on Project MUSE., 2019)
"When hurricanes, earthquakes, wildfires, and other disasters strike, we count our losses, search for causes, commiserate with victims, and initiate relief efforts. Amply illustrated and expansively researched, 'Inventing Disaster' explains the origins and development of this predictable, even ritualized, culture of calamity over three centuries, exploring its roots in the revolutions in science, information, and emotion that were part of the Age of Enlightenment in Europe and America"--